Antibody-Mediated Targeting of Antigens to Intestinal Aminopeptidase N Elicits Gut IgA Responses in Pigs - Van der Weken, Hans; Sanz Garcia, Raquel; Sanders, Niek N.; Cox, Eric; Devriendt, Bert (Frontiers in Immunology, 2021)
Many pathogens enter the host via the gut, causing disease in animals and humans. A robust intestinal immune response is necessary to protect the host from these gut pathogens. Despite being best suited for eliciting intestinal immunity, oral vaccination remains a challenge due to the gastrointestinal environment, a poor uptake of vaccine antigens by the intestinal epithelium and the tolerogenic environment pervading the gut. To improve uptake, efforts have focused on targeting antigens towards the gut mucosa. An interesting target is aminopeptidase N (APN), a conserved membrane protein present on small intestinal epithelial cells shown to mediate epithelial transcytosis. Here, we aimed to further optimize this oral vaccination strategy in a large animal model. Porcine APN-specific monoclonal antibodies were generated and the most promising candidate in terms of epithelial transcytosis was selected to generate antibody fusion constructs, comprising a murine IgG1 or porcine IgA backbone and a low immunogenic antigen: the F18-fimbriated E. coli tip adhesin FedF. Upon oral delivery of these recombinant antibodies in piglets, both mucosal and systemic immune responses were elicited. The presence of the FedF antigen however appeared to reduce these immune responses. Further analysis showed that F18 fimbriae were able to disrupt the antigen presenting capacity of intestinal antigen presenting cells, implying potential tolerogenic effects of FedF. Altogether, these findings show that targeted delivery of molecules to epithelial aminopeptidase N results in their transcytosis and delivery to the gut immune systems. The results provide a solid foundation for the development of oral subunit vaccines to protect against gut pathogens.